Inside Back Cover: Highly Organized Ferrocene‐Functionalized Nanoporous Silica Films with an Extremely Fast Electron‐Transfer Rate for an Intrinsically Nonconducting Oxide‐Modified Electrode (ChemElectroChem 11/2015). Issue 11 (23rd October 2015) - Audebert, Pierre; Vilà, Neus; Allain, Clémence; Maisonneuve, Franck; Walcarius, Alain; Hapiot, Philippe
Abstract : The Inside Back Cover illustrates the fast electron hopping that can be observed for a non‐intrinsically conducting electrode. More details can be found in the Article by P. Audebert, A. Walcarius, P. Hapiot et al. onpage 1695 in Issue 11, 2015 (DOI:10.1002/celc.201500227 ).